Organizational Culture and Sustainability in Turbulent Environments. Insights from a Case-Study of a Large Mining MNC in a Latin America Country (2006)
A "strong company culture" has been usually deemed the sine qua non of success in organizations. As a consequence, the interplay between organizational culture and company's performance is a critical issue in organization studies needed of empirical research to surpass management conventional wisdom. Moving in that direction, this paper -based upon a in depth study of a large mining MNC operating in rural Colombia-shows that organizational culture has played an important role in the company's sustainability for over three decades (1970-2003) in a particularly conflicting and turbulent environment. The case study was based on a qualitative methodology that included the realization of almost one hundred in-depth interviews with a variety of stakeholders, field observations, and a review of secondary sources on the company. The paper consists of six parts. The first part presents the methodology employed in conducting the case study. The second and third sections present basic information about the mining company and its environment. The fourth part shows the process through which, over time, certain distinctive values of the company organizational culture emerged: two of these through collective creative efforts and the other through deliberate efforts by management. The fifth part brings together theoretical elements proposed by W. Ouchi to demonstrate that the values cited, together with the bureaucratic and technological characteristics of the organization, make up an elaborate control system, which in turn is a core competency and source of competitive advantage that the mining company maintained in 2003. The final section presents conclusions and a discussion of the importance of this study for future research.